Similar Morphological and Functional Training Adaptations Occur Between Continuous and Intermittent Blood Flow Restriction. Issue 7 (July 2021) - Davids, Charlie J.; Raastad, Truls; James, Lachlan P.; Gajanand, Trishan; Smith, Emily; Connick, Mark; McGorm, Hamish; Keating, Shelley; Coombes, Jeff S.; Peake, Jonathan M.; Roberts, Llion A.
Abstract : Abstract: Davids, CJ, Raastad, T, James, L, Gajanand, T, Smith, E, Connick, M, McGorm, H, Keating, S, Coombes, JS, Peake, JM, and Roberts, LA. Similar morphological and functional training adaptations occur between continuous and intermittent blood flow restriction. J Strength Cond Res 35(7): 1784–1793, 2021—The aim of the study was to compare skeletal muscle morphological and functional outcomes after low-load resistance training using 2 differing blood flow restriction (BFR) protocols. Recreationally active men and women ( n = 42 [f = 21], 24.4 ± 4.4 years) completed 21 sessions over 7 weeks of load-matched and volume-matched low-load resistance training (30% 1 repetition maximum [1RM]) with either (a) no BFR (CON), (b) continuous BFR (BFR-C, 60% arterial occlusion pressure [AOP]), or (c) intermittent BFR (BFR-I, 60% AOP). Muscle mass was assessed using peripheral quantitative computed tomography before and after training. Muscular strength, endurance, and power were determined before and after training by assessing isokinetic dynamometry, 1RM, and jump performance. Ratings of pain and effort were taken in the first and final training session. An alpha level of p < 0.05 was used to determine significance. There were no between-group differences for any of the morphological or functional variables. The muscle cross sectional area (CSA) increased pre-post training ( p = 0.009; CON: 1.6%, BFR-C: 1.1%, BFR-I: 2.2%). Maximal isometric strength increased pre-post training ( p < 0.001; CON: 9.6%, BFR-C: 14.3%, BFR-I: 19.3%). Total work performed during an isokinetic endurance task increased pre-post training ( p < 0.001, CON: 3.6%, BFR-C: 9.6%, BFR-I: 11.3%). Perceptions of pain ( p = 0.026) and effort ( p = 0.033) during exercise were higher with BFR-C; however, these reduced with training ( p = 0.005–0.034). Overall, these data suggest that when 30% 1RM loads are used with a frequency of 3 times per week, the addition of BFR does not confer superior morphological or functional adaptations in recreationally active individuals. Furthermore, the additional metabolic stress that is proposed to occur with a continuous BFR protocol does not seem to translate into proportionally greater training adaptations. The current findings promote the use of both intermittent BFR and low-load resistance training without BFR as suitable alternative training methods to continuous BFR. These approaches may be practically applicable for those less tolerable to pain and discomfort associated with ischemia during exercise. Abstract : Supplemental Digital Content is Available in the Text.